Choosey journalists choose GIFs - Gil, Jodie Mozdzer (The Quill, 2016)
The still photographs incorporate subtle movement, such as wind blowing grass or eyes blinking, that play on repeat through an animated GIF. [...]don't make your readers seasick with too much movement or too many GIFs on the same page.t
Num Pages: 1 Place: Indianapolis, United States
Keywords: Digital broadcasting; Photographs; School districts; Software reviews; Video recordings; dept.jrn

With data, educate yourself and start simple - Gil, Jodie Mozdzer (The Quill, 2015)
The data sets have a variety of content, including farmers market locations, school absentee rates and crime statistics. START SIMPLE The downloadable data can be as simple as a spreadsheet chronicling one data point over time - for example, the amount of money the federal government has spent on school food programs since 1969.
Num Pages: 1 Place: Indianapolis, United States
Keywords: Criminal statistics; Databases; Datasets; Digital broadcasting; Journalism; Journalists; Trends; dept.jrn